2014
DOI: 10.5539/cis.v7n1p41
|View full text |Cite
|
Sign up to set email alerts
|

SAAS: Creation of an e-Advising Tool to Augment Traditional Advising Methods

Abstract: Advising is a vital component of student academic success in college. This paper describes the design and creation of an electronic Student Academic Advising System (SAAS) to support conventional advising procedures. Use of this SAAS is intended to better guide students through educational process via the use of technology applications.In addition to evaluating the impact of academic e-advising on the student experience in higher education, this study also explores the two different types of advising (e-advisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Garger et al (2010), for example, investigated the new perceptions of future student performance which is based on reviewed literature with a non-experimental design of a model of student's social integration and GPA prediction. Shana and Abdullah (2014) described the design and creation of electronic Academic Advisor System termed as SAAS to support conventional procedures of a human advisor. Kouatli (2015) used hybrid intelligent technique composed of fuzzy logic and, genetic Algorithm to prototype a decision support system to predict the future GPA level for students during the admission process depending on the student performance of high school, sophomore exam and an English exam.…”
Section: Academic Advisor System: a Student Questionnairementioning
confidence: 99%
“…Garger et al (2010), for example, investigated the new perceptions of future student performance which is based on reviewed literature with a non-experimental design of a model of student's social integration and GPA prediction. Shana and Abdullah (2014) described the design and creation of electronic Academic Advisor System termed as SAAS to support conventional procedures of a human advisor. Kouatli (2015) used hybrid intelligent technique composed of fuzzy logic and, genetic Algorithm to prototype a decision support system to predict the future GPA level for students during the admission process depending on the student performance of high school, sophomore exam and an English exam.…”
Section: Academic Advisor System: a Student Questionnairementioning
confidence: 99%
“…Several studies have investigated the impact of academic e-Advising on students. Zuhrieh and Shubair (2014) revealed that students appear to favor a blended advising approach. In such an approach, the advising process utilizes an e-Advising system and traditional face-to-face advising.…”
Section: Literature Review Academic Advicementioning
confidence: 99%
“…Other custom solutions have been developed such as a custom "e-advising" tool. Such a tool includes the means to create custom study plans as well as a schedule builder [6].…”
Section: Literature Reviewmentioning
confidence: 99%